Iowa RBA, December 9, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for December 9, 1996. Highlights of the update include the return of a Pinyon Jay, as well as sightings of a Long-tailed Duck, Red Crossbills, all three Scoter species, and a Varied Thrush. Other interesting observations include two Pomarine Jaegers, a first year Glaucous Gull, and Snowy Owls. Also included are handwritten notes for the next week's update with sightings of Thayer's Gulls and a Cape May Warbler. Epson - sheet feed/flatbed